Returning Uluru. (31st August 2020) - Bickersteth, Julian; West, David; Wallis, David
ABSTRACT: Uluru, once known as Ayer's Rock, is one of Australia's most well-known natural phenomena. A World Heritage Site, it is listed for its cultural and natural heritage attributes. Until recently it had been visited by more than 300, 000 people annually, many of whom climbed the rock, despite the expressly stated wishes of the Traditional Owners that they should not. In November 2017, the Uluru Kata Tjuta National Park authority decided to permanently close the Uluru climb and remove the climb infrastructure, which included a series of 134 posts cemented into the rock and linked by chain, with a cairn at the summit. This paper details the conservation processes and remediating materials considered, then the methods employed to remove this infrastructure safely. Technical requirements included leaving no visible evidence of the posts, avoiding or minimising any damage to the rock surface, and providing a long-lasting in-fill solution that would blend into the rock surface, on the basis that the rock would never be climbed again. The logistics of a site which is some 470 km from the nearest town, has no facilities, and where the surface temperature can reach 60–70°C in mid summer, determined the removal of the evidence of human intervention on the rock site of Uluru. The broader context of Uluru's recent history and its hand-back to the traditional owners is also discussed.